Design, synthesis and structure–activity relationships of mangostin analogs as cytotoxic agents. Issue 72 (12th December 2018) - Chi, Xiao-Qian; Zi, Cheng-Ting; Li, Hong-Mei; Yang, Liu; Lv, Yong-Feng; Li, Jin-Yu; Hou, Bo; Ren, Fu-Cai; Hu, Jiang-Miao; Zhou, Jun
Abstract : A series xanthone derivatives were synthesized and cytotoxicity results indicated that the isopentene group at C-8 is essential. Abstract : In order to better understand the structure–activity relationship of mangostin, a series of xanthone derivatives based on α-mangostin were designed and synthesized. All the compounds were evaluated for their cytotoxicity against a panel of five human cancer cell lines (HL-60, SMMC-7721, A-549, MCF-7 and SW480) using MTT assays. Most of them showed cytotoxicity and most of all, compounds1a and2h showed the highest cytotoxic potency by HL-60 cancer cell lines with IC50 values of 5.96 μM and 6.90 μM respectively; compound3e showed the highest cytotoxic potency against SMMC-7221 cancer cell line with IC50 values of 3.98 μM; compounds2e and2m showed lower cytotoxicity but higher selectivity than α-mangostin against HL-60 and SMMC-7221 cancer cell lines respectively. Structure–activity relationship analysis indicates that the maintenance of the isopentene group at C-8 is essential for the cytotoxic activity.